Oil reservoirs, an exceptional habitat for microorganisms - Pannekens, Mark (N Biotechnol, 2019)
Microorganisms are present in oil reservoirs around the world where they degrade oil and lead to changes in oil quality. Unfortunately, our knowledge about processes in deep oil reservoirs is limited due to the lack of undisturbed samples. In this review, we discuss the distribution of microorganisms at the oil-water transition zone as well as in water saturated parts of the oil leg and their possible physiological adaptations to abiotic and biotic ecological factors such as temperature, salinity and viruses. We show the importance of studying the water phase within the oil, because small water inclusions and pockets within the oil leg provide an exceptional habitat for microorganisms within a natural oil reservoir and concurrently enlarge the zone of oil biodegradation. Environmental factors such as temperature and salinity control oil biodegradation. Temperature determines the type of microorganisms which are able to inhabit the reservoir. Proteobacteria and Euryarchaeota, are ubiquitous in oil reservoirs over all temperature ranges, whereas some others are tied to specific temperatures. It is proposed that biofilm formation is the dominant way of life within oil reservoirs, enhancing nutrient uptake, syntrophic interactions and protection against environmental stress. Literature shows that viruses are abundant in oil reservoirs and the possible impact on microbial community composition due to control of microbial activity and function is discussed.